2007
DOI: 10.1021/jm061257w
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Rhodanine Class of Compounds as Inhibitors of Plasmodium falciparum Enoyl-Acyl Carrier Protein Reductase

Abstract: Enoyl acyl carrier protein (ACP) reductase, one of the enzymes of the type II fatty acid biosynthesis pathway, has been established as a promising target for the development of new drugs for malaria. Here we present the discovery of a rhodanine (2-thioxothiazolidin-4-one) class of compounds as inhibitors of this enzyme using a combined approach of rational selection of compounds for screening, analogue search, docking studies, and lead optimization. The most potent inhibitor exhibits an IC(50) of 35.6 nM again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(28 citation statements)
references
References 46 publications
(92 reference statements)
0
28
0
Order By: Relevance
“…An independent study subsequently reported modest PfENR inhibition with a remarkably similar set of pyrazoles (57). These researchers also reported the discovery of a rhodanine class of small molecule binders to PfENR, with the most efficacious member of this class approximating the activity of triclosan (58). Building on initial investigations into plant polyphenols as antibacterial FAS-II inhibitors (59), other researchers have independently examined natural product inhibitors of PfENR where a common structural theme is the presence of one or more phenolic moieties (60,61).…”
Section: Journal Of Biological Chemistry 25439mentioning
confidence: 93%
“…An independent study subsequently reported modest PfENR inhibition with a remarkably similar set of pyrazoles (57). These researchers also reported the discovery of a rhodanine class of small molecule binders to PfENR, with the most efficacious member of this class approximating the activity of triclosan (58). Building on initial investigations into plant polyphenols as antibacterial FAS-II inhibitors (59), other researchers have independently examined natural product inhibitors of PfENR where a common structural theme is the presence of one or more phenolic moieties (60,61).…”
Section: Journal Of Biological Chemistry 25439mentioning
confidence: 93%
“…While carrying out the microwave-assisted FriedlĂ€nder synthesis of quinoline derivatives, AsĂ­s et al found that a series of substituted quinolines 107 possessed promising activities against P. falciparum and other parasites causative of leishmaniasis, sleeping sickness and Chagas disease [146]. Compounds 107a, and 107b were most active against P. falciparum with IC 50 docking and lead optimization to discover quinolines as inhibitor of PfENR, and most promising inhibitor 108 exhibited an IC 50 value of 50.0 mM [147]. Antimalarial chalcones and vinyl sulfones are believed to act against malarial cysteine proteases [148,149].…”
Section: Ring-modified Quinolines (Figs 15e17)mentioning
confidence: 99%
“…We had recently conducted a diversity-set screening against PfENR and identified a new scaffold-rhodanine with nanomo-lar inhibition constant (24). The mechanism of inhibition was probed and the inhibitors were found to be competitive with respect to the substrate and noncompetitive with respect to the cofactor NADH.…”
Section: Introductionmentioning
confidence: 99%